Inciting joy : essays - Gay, Ross, 1974- (Algonquin Books of Chapel Hill, 2022)
"A collection of long-form essays on joy, in which the author turns his curious and poetic mind to everything from skateboarding and cover songs, basketball and race, dancing and academia, death and laughter, and, always, the garden and the natural world"--